UTILISATION OF PHYSICAL ENVIRONMENT IN STUDENT CHARACTER BUILDING: BOARDING SCHOOL - Abdul Mughis; Ria Arista Asih (JURNAL EDUSCIENCE, 2026)
Purpose - The aims of this study are expected to provide an in-depth understanding of how the school's physical environment positively influences students' character development. In addition, this study is expected to inform school management in developing and expanding green spaces as a character education strategy that focuses not only on academics but also on students' moral and social development.Methodology - The approach in this research is qualitative, supported by descriptive data, data collection using interview techniques, consisting of the principal, vice principal for facilities and infrastructure, and vice principal Maintenance environment. Data analysis techniques use the Miles and Huberman approach, namely data reduction, data display, and conclusion drawing.Findings - This study collected 4 significant findings, namely 1) the school does not have documents that support the green environment management programme as a student character builder, but the school environment is good enough. 2) Students are motivated by the existence of a beautiful physical environment. 3) The school has not focused on character building. However, the field evidence shows that almost all environmental programmes have a positive influence on changes in student character. 4) A good physical environment can relieve student stressContribution - This research provides scientific facts on the utilisation of the physical environment for character building, based on data collected by researchers, to serve as a reference and consideration for policies aimed at both the development of school green land and student character education.